ANALISIS KONTEN PADA IKLAN KECANTIKAN SHAMPOO SUNSILK: MODEL INTERACTIVE DAN CONVERSATIONAL - Hilda Hastuti (LPPM Universitas Bumigora Mataram, 2018)
In general, the advertisement created for a different purpose. The language of advertisement typically use persuasive that aims to attract the attention of consumers. This research is qualitative research namely analysis of content with interactive and converstional models. Interactive was found that advertisement maker has a point of view that all consumers have the same position. Whereas in conversationally was found that the advertisment maker has the purpose to persuade consumers as well as instill the belief in the community that the shampoo can provide best solution of consumers’ hair. The advertisments that are served to be able to master the social cultural market and manufacturers can get benefit in social cultural market.